2003
DOI: 10.1038/sj.cgt.7700646
|View full text |Cite
|
Sign up to set email alerts
|

Complete tumor prevention by engineered tumor cell vaccines employing nonviral vectors

Abstract: We report that 100% mice survival after tumor challenge is achieved with cytokine-engineered cells employing nonviral lipoplexes and without using viral vectors. We describe this effect with cytokine-secreting tumor cell vaccines, based on cell clones or fresh transfected cells. Tumor cells were transfected with murine granulocyte-macrophage colony-stimulating factor (GM-CSF) or IL-4 plasmids employing the cationic lipid DOTAP, were irradiated (150 Gy) and kept frozen until use. The transfection efficacy was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…27,[52][53][54][55] Interestingly, many cell vaccination studies for cancer therapy have focused on using GM-CSF as the preferred cytokine of choice based on initial data that identified it to be the best cytokine. [56][57][58][59][60] However, in the initial comparison study IL-12 was not tested, 56 and at least one recent study suggests that very high doses of GM-CSF can result in adverse immunosuppressive effects. 61 Taken together, the above-cited studies suggest that IL-12 might be the better cytokine for inducing a more robust antitumoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…27,[52][53][54][55] Interestingly, many cell vaccination studies for cancer therapy have focused on using GM-CSF as the preferred cytokine of choice based on initial data that identified it to be the best cytokine. [56][57][58][59][60] However, in the initial comparison study IL-12 was not tested, 56 and at least one recent study suggests that very high doses of GM-CSF can result in adverse immunosuppressive effects. 61 Taken together, the above-cited studies suggest that IL-12 might be the better cytokine for inducing a more robust antitumoral immunity.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of irradiation on IL-12 production could be explained by the cytokine leakage from radiation-damaged cells or by a radiation-induced activation of transcription factors. 41,42 This effect on cytokine production seems to be cell-or cytokine-dependent as Rosenthal et al 43 reported a five-fold increase in granulocyte-macrophage colony-stimulating factor production after irradiation of genetically modified murine cells, whereas Moret-Tatay et al 44 reported a decay in RNA production in genetically (granulocyte-macrophage colony-stimulating factor) modified tumor cells. Santin et al 45 reported no effect of irradiation on IL-12 production by the genetically modified human ovarian tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Currently, some studies have reported that commercially available transfection reagents (i.e., Lipoplexes) have proved useful for nonviral gene therapy. [31][32][33][34][35] We too are very interested in these reagents. Nevertheless, we expect that targeted gene therapy by sonoporation using contrast agents for HCC would be a much easier method, based on our experience using contrast agents to detect hepatic tumors by US examination in clinical situations.…”
Section: Discussionmentioning
confidence: 99%